ANALISIS STRUKTUR NUCLEAR REACTOR COMPARTMENT PADA NUCLEAR POWERED SHIP DENGAN MENGGUNAKAN METODE FINITE ELEMENT ANALYSIS - Adara Maysa Ananta Pasa; Budianto Budianto; Renanda Nia Rachmadita (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
In the shipbuilding sector, nuclear reactors are one component that important in nuclear powered ships. A ship that has an identity as a nuclear powered ship has been applied in various developed countries to be used as war interests and as an icebreaker. Its like radioisotope, until now it has experienced growth and regeneration in the fourth, where generation IV is called the most innovative reactor. The best known technology is PWR. However, this PWR will be simplified in the concept of being small compartment. The concept will be a compartment structure analysis concept at the writing of this thesis. Therefore, this analysis is carried out to find out how to analyse the compartment structure in its application on nuclear powered vessels. The reactor’s nuclear compartment design will be analysed with autodesk fusion 360. The method used id finite element analysis. The compartment structure conditions that will be discussed are when exposed within effect of neutron. These condition, will be examined from changes in material properties and how the results of the efficiency of stress and strain in small compartment nuclear reactors. The material used is stainless steel 304, steel and polyethylene. The efficiency result obtained were 4,77%.